1983
DOI: 10.1007/bf00154702
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing of the palpebral fissure in diabetes

Abstract: In 204 adult, white diabetics the palpebral fissure was measured and related to the state of metabolic control of the diabetes. A control group was formed of 204 persons matched by age and sex. The average palpebral fissure in the control group was 9.9 mm: there was a slight, but not significant, difference between the age groups and the sexes. In diabetics who were not insulin dependent the average width of the palpebral fissure was found to be 9.4 mm; in severe chronic deregulation of the diabetes, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…Although Müller's muscle is admittedly dependent on sympathetic stimulation, it can also be influenced by other factors such as gaze direction, flexion or extension of the neck, and orbicularis oculi tone. We found a small, although highly significant difference in PFH between the treated eye and the untreated eye (∆PFH), in accordance with the measures reported by Bastiaensen et al 6 in a cohort of patients with insulin-dependent diabetes. The ∆PFH response in healthy particpants 3 5 is up to 70% higher in comparison with our measures, indicating a loss of sympathetic reserve capacity caused by decreased adrenergic excitability and autonomic dysfunction .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although Müller's muscle is admittedly dependent on sympathetic stimulation, it can also be influenced by other factors such as gaze direction, flexion or extension of the neck, and orbicularis oculi tone. We found a small, although highly significant difference in PFH between the treated eye and the untreated eye (∆PFH), in accordance with the measures reported by Bastiaensen et al 6 in a cohort of patients with insulin-dependent diabetes. The ∆PFH response in healthy particpants 3 5 is up to 70% higher in comparison with our measures, indicating a loss of sympathetic reserve capacity caused by decreased adrenergic excitability and autonomic dysfunction .…”
Section: Discussionsupporting
confidence: 92%
“…DAN leads to sympathetic paresis characterized by miosis and ptosis. 6 , 8 Pupillary denervation hypersensitivity to phenylephrine has been shown in diabetes 10 , 11 ; however, to our knowledge, denervation hypersensitivity to phenylephrine has not been investigated in DAN. In the case of denervation hypersensitivity, an increased ∆PFH response would be expected.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bastiaensen assumed that the cause of acute blepharoptosis in patients with diabetes is mostly oculomotor nerve palsy [ 23 ]. In another report, Bastiaensen identified blepharoptosis comorbidity in a large number of patients with diabetes and presumed that this finding may have been related to chronic tissue hypoxia, to which the levator palpebrae muscle is extra-sensitive, and in which thickening of the basal membrane of the capillaries may be an important factor [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that blepharoptosis is related to systemic diseases, such as hypertension, diabetes, dyslipidemia, and obesity 16,17,22,[26][27][28][29] . In these reports, the causative mechanisms of these relationships were suggested to be end-organ damage related to metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%